A review of the additive health risk of cannabis and tobacco co-use - Meier, Ellen; Hatsukami, Dorothy K. (Drug and alcohol dependence, 2016)
•Few co-use studies examine toxicant exposure.•It is unclear whether co-use causes additive toxicant exposure.•“Chasing” marijuana with a tobacco cigarette does not appear to affect CO.•Marijuana dosage does not appear to affect CO or topography.•Prevalence of ENDs and marijuana co-use is low, but may be growing. Cannabis and tobacco are the most widely used substances, and are often used together. The present review examines the toxicant exposure associated with co-use (e.g., carbon monoxide, carcinogens), co-use via electronic nicotine delivery systems (ENDS), and problematic methodological issues present across co-use studies. An extensive literature search through PubMed was conducted and studies utilizing human subjects and in vitro methods were included. Keywords included tobacco, cigarette, e-cigarette, ENDS, smoking, or nicotine AND marijuana OR cannabis OR THC. Co-use may pose additive risk for toxicant exposure as certain co-users (e.g., blunt users) tend to have higher breath carbon monoxide levels and cannabis smoke can have higher levels of some carcinogens than tobacco smoke. Cannabis use via ENDS is low and occurs primarily among established tobacco or cannabis users, but its incidence may be increasing and expanding to tobacco/cannabis naïve individuals. There are several methodological issues across co-use research including varying definitions of co-use, sample sizes, lack of control for important covariates (e.g., time since last cigarette), and inconsistent measurement of outcome variables. There are some known additive risks for toxicant exposure as a result of co-use. Research utilizing consistent methodologies is needed to further establish the additive risk of co-use. Future research should also be aware of novel technologies (e.g., ENDS) as they likely alter some toxicant exposure when used alone and with cannabis.